1998
DOI: 10.1006/mchj.1998.1654
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Curing Temperature on the Leachability of Lead Undergoing Solidification/Stabilization with Cement

Abstract: Curing temperature was found to dramatically affect the amount of waste leached from a solidified waste/cement matrix between 2 and 40°C. Using lead nitrate as a model waste, samples cured for 7, 14, and 28 days at a cure temperature of 40°C leached very little lead (1-3 mg/liter), while at a cure temperature of 2°C samples leached approximately 25 times more lead (20 -90 mg/liter). The results indicate that curing temperature is a very crucial variable to consider when solidifying waste with cement if maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The rate of hydration was reported to be insensitive to temperature over a range of 0-40 • C. Janusa et al [54] reported that the lower curing temperatures of a lead bearing waste/cement matrix decreases the solubility of lead salts formed in the cement, resulting in an increase in gelatinous coatings on grains. This increase of coating at lower curing temperatures, causes less contact between cement grains and water, retarding the hydration process and the solidifying/stabilizing power of cement.…”
Section: Initial Setting Time and Hydrationmentioning
confidence: 97%
“…The rate of hydration was reported to be insensitive to temperature over a range of 0-40 • C. Janusa et al [54] reported that the lower curing temperatures of a lead bearing waste/cement matrix decreases the solubility of lead salts formed in the cement, resulting in an increase in gelatinous coatings on grains. This increase of coating at lower curing temperatures, causes less contact between cement grains and water, retarding the hydration process and the solidifying/stabilizing power of cement.…”
Section: Initial Setting Time and Hydrationmentioning
confidence: 97%